The Role of Immune and Epithelial Stem Cells in Inflammatory Bowel Disease Therapy - Binienda, Agata; Ziolkowska, Sylwia; Hauge, Ingvild H.; Salaga, Maciej (Current Drug Targets, 2020)
Background: Inflammatory Bowel Disease (IBD) is categorized as Crohn’s disease (CD) and Ulcerative colitis (UC) and is characterized by chronic inflammation in the gastrointestinal (GI) tract. Relapsing symptoms, including abdominal pain, increased stool frequency, loss of appetite as well as anemia contribute to significant deterioration of quality of life. IBD treatment encompasses chemotherapy (e.g. corticosteroids, thiopurines) and biological agents (e.g. antibodies targeting tumour necrosis factor α, interleukin 12/23) and surgery. However, efficacy of these therapies is not satisfactory. Thus, scientists are looking for new options in IBD treatment that could induce and maintain remission. Objective: To summarize previous knowledge about role of different intestinal cells in IBD pathophysiology and application of stem cells in the IBD treatment. Results: Recent studies have emphasized an important role of innate lymphoid cells (ILCs) as well as intestinal epithelial cells (IECs) in the IBD pathophysiology suggesting that these types of cells can be new targets for IBD treatment. Moreover, last studies show that stem cells transplantation reduces inflammation in patients suffering from IBD, which are resistant to conventional therapies. Conclusion: Both hematopoietic stem cells (HSCs) and mesenchymal stem cells (MSCs) are able to restore damaged tissue and regulate the immune system. Autologous HSCs transplantation eliminates autoreactive cells and replace them with new T-cells resulting a long-time remission. Whereas MSCs transplantation is effective therapy in one of the major complications of IBD, perianal fistulas.
Keywords: innate lymphoid cells